Hubungan efikasi diri dengan mekanisme koping siswa dalam menghadapi tugas di SMA Negeri 1 Jember - Regita Sari Dwi Cahyani; Erti Ikhtiarini Dewi; Enggal Hadi K (UPT Percetakan dan Penerbitan Universitas Jember, 2022)
Adolescence period is a transition period of human development between childhood and adulthood starting at the age of 12 or 13 years and ending at the last teenage years. Teenagers are in a high school period. In this period, teenagers undergo stress since they faced various jobs or tasks simultaneously, such as school assignments, and the burden of learning which was felt quite hard. Moreover, High School is currently following the 2013 curriculum by applying the Semester Credit Unit where students are required to find out in advance to do the assignments. Teenagers needed the confidence to resolve the demands of school duties. This study identified the relationship between self-efficacy and student coping mechanisms in dealing with assignments. The research design applied correlation analysis with a cross-sectional approach. The data collection technique used was stratified random sampling with 243 respondents. Data collection was carried out using the self-efficacy questionnaire and Children's Coping Questionary. The results of data analysis performed the Pearson correlation that revealed a score of p-value 0.00; r: 0.332; meaning that there was a relationship between self-efficacy and coping mechanisms of students in facing assignments in SMA 1 Jember. Therefore, it was needed teachers and parents support in providing motivation to students so that their self-efficacy of students was able to increase and produce an adaptive coping mechanism.